The Effect of Different Antihypertensive Treatment Methods on Endothelial Functions in Patients With Chronic Renal Failure on Hemodialysis - Yesil Gunal, Servin; Ustundag, Bilal; Gunal, Ali Ihsan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2010)
Hypervolemia and uremic toxins result in accelerated atherosclerosis in chronic renal failure by causing endothelial dysfunction hypertension. The vast majority of patients undergoing renal replacement therapy are hypertensive and hypervolemic. It is accepted that these two risk factors are the most important causes of mortality. While five-year survival in hemodialysis patients using antihypertensive drugs is 40-50%, ten-year survival in hemodialysis patients applied strict volume control is 70%. MATERIAL and Method: The study was composed of three groups as follows: control group (n=30), hemodialysis patients (normotensive with hypotensive drugs HDdrug, n=30), hemodialysis patients (normotensive with strict volume control HDvc, n=30). von Willebrand factor (vWF), D-dimer, nitric oxide (NO), homocysteine and routine biochemical parameters were studied in all groups. Results: Although the interdialytic weight gain of the hemodialysis patients using antihypertensive drugs was higher than hemodialysis patients applied strict volume control (p<0.001), the blood pressure of the drug users was within the acceptable levels. However, the levels of vWF, and, D-dimer in patients applied volume control were lower than that of HDdrug. Conclusion: In conclusion, although antihypertensive drugs can decrease elevated blood pressure to a limited extent in dialysis patients, they cannot improve the endothelial dysfunction. Elevated blood pressure and endothelial dysfunction are controlled effectively with volume control.
Keywords: Chronic renal failure; Endothelium; Volume control; Antihypertensives